Egypt's COVID-19 Recent Happenings and Perspectives: A Mini-Review - Saied, AbdulRahman A.; Metwally, Asmaa A.; Madkhali, Norah Abdullah Bazekh; Haque, Shafiul; Dhama, Kuldeep (Frontiers in Public Health, 2021)
The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has affected countries across the world. While the zoonotic aspects of SARS-CoV-2 are still under investigation, bats and pangolins are currently cited as the animal origin of the virus. Several types of vaccines against COVID-19 have been developed and are being used in vaccination drives across the world. A number of countries are experiencing second and third waves of the pandemic, which have claimed nearly four million lives out of the 180 million people infected globally as of June 2021. The emerging SARS-CoV-2 variants and mutants are posing high public health concerns owing to their rapid transmissibility, higher severity, and in some cases, ability to infect vaccinated people (vaccine breakthrough). Here in this mini-review, we specifically looked at the efforts and actions of the Egyptian government to slow down and control the spread of COVID-19. We also review the COVID-19 statistics in Egypt and the possible reasons behind the low prevalence and high case fatality rate (CFR%), comparing Egypt COVID-19 statistics with China (the epicenter of COVID-19 pandemic) and the USA, Brazil, India, Italy, and France (the first countries in which the numbers of patients infected with COVID-19). Additionally, we have summarized the SARS-CoV-2 variants, vaccines used in Egypt, and the use of medicinal plants as preventive and curative options.